In Situ Biodiesel Production from Residual Oil Recovered from Spent Bleaching Earth - Ramli Mat; Ow Shin Ling; Anwar Johari; Mahadhir Mohamed (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2011)
Currently, semi-refined and refined vegetable oils are used as a feedstock in biodiesel production. However, due to competition with conventional fossil fuel, economic reasons, shortage supply of food and its social impact on the global scale has somewhat slowed the development of biodiesel industry. Studies have been conducted to recover oil from mill palm oil operation especially from the spent bleaching earth. Hence, the study was to investigate the potential recovery of oil from spent bleaching earth to be used as a feedstock for biodiesel production. The effect of different types of catalysts (sodium hydroxide alkali and sulfuric acid catalysts) on biodiesel yield was studied. In addition, the effect of volume addition of methanol to the weight of spent bleaching earth on the product yield was also studied. Furthermore, the effect of ratio of hexane to methanol was also carried out to determine its product yield. The studies were carried out in an in-situ biodiesel reactor system and the biodiesel product was analyzed using gas chromatography mass spectrometry. Result shows that the use of alkali catalyst produced the highest yield of biodiesel and the most optimum biodiesel yield was obtained when the methanol to spent bleaching earth ratio was 3.2:1 (gram of methanol: gram of SBE) and hexane to methanol ratio of 0.6:1 (volume of hexane: volume of methanol). © 2011 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)